Periostin promotes renal cyst growth and interstitial fibrosis in polycystic kidney disease - Wallace, Darren P. (2013)
In renal cystic diseases, sustained enlargement of fluid-filled cysts is associated with severe interstitial fibrosis and progressive loss of functioning nephrons. Periostin, a matricellular protein, is highly overexpressed in cyst-lining epithelial cells of autosomal dominant polycystic disease kidneys (ADPKD) compared to normal tubule cells. Periostin accumulates in situ within the matrix subjacent to ADPKD cysts, binds to α(V)β(3)- and α(V)β(5)-integrins and stimulates the integrin-linked kinase to promote cell proliferation. We knocked out periostin (Postn) in pcy/pcy mice, an orthologous model of nephronophthisis type 3, to determine whether periostin loss reduces PKD progression in a slowly progressive model of renal cystic disease. At 20 weeks of age, pcy/pcy: Postn−/− mice had a 34% reduction in kidney weight/body weight, a reduction in cyst number and total cystic area, a 69% reduction in phosphorylated S6, a downstream component of the mTOR pathway, and fewer proliferating cells in the kidneys compared to pcy/pcy: Postn+/+ mice. The pcy/pcy Postn knockout mice also had less interstitial fibrosis with improved renal function at 20 weeks and significantly longer survival (51.4 compared to 38.0 weeks). Thus, periostin adversely modifies the progression of renal cystic disease by promoting cyst epithelial cell proliferation, cyst enlargement and interstitial fibrosis, all contributing to the decline in renal function and premature death.